1998
DOI: 10.2108/zsj.15.11
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Dependence of the Axotomy-Induced Long-Lasting Firing in an Identified Crayfish Motoneuron

Abstract: I have reported previously that axotomy of an identifiable anal motoneuron of crayfish Procambarus clarkii induces a long-lasting firing and that a prolonged depolarizing pulse to its cut end can induce a similar response. In this study, I confirmed that this stimulus is comparable to axotomy; the frequency of stimulus-induced firing increases linearly with the stimulus intensity and its firing pattern is the same as that following axotomy. Then, when the cut end was bathed for more than 1 hr in test solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
(38 reference statements)
0
12
1
Order By: Relevance
“…The present axonal segment preparation contained other units than AML (Muramoto, 1977(Muramoto, , 1993, but they did not exhibit SF in this study. In crayfish and lobsters, axons can survive, conduct action potentials and release transmitters for months after being separated from their somata (Hoy et al, 1967;Wine, 1973;Bittner and Johnson, 1974;Atwood et al, 1989;Blundon et al, 1990;Parnas et al, 1991), yet none of them have shown prolonged spontaneous firing (Titmus and Faber, 1990;Bittner, 1991).…”
Section: Spontaneous Firing In An Anucleate Aml Axonal Segmentmentioning
confidence: 59%
See 4 more Smart Citations
“…The present axonal segment preparation contained other units than AML (Muramoto, 1977(Muramoto, , 1993, but they did not exhibit SF in this study. In crayfish and lobsters, axons can survive, conduct action potentials and release transmitters for months after being separated from their somata (Hoy et al, 1967;Wine, 1973;Bittner and Johnson, 1974;Atwood et al, 1989;Blundon et al, 1990;Parnas et al, 1991), yet none of them have shown prolonged spontaneous firing (Titmus and Faber, 1990;Bittner, 1991).…”
Section: Spontaneous Firing In An Anucleate Aml Axonal Segmentmentioning
confidence: 59%
“…Although the AML axon can show a prolonged firing following axotomy (Muramoto, 1993), axotomy-induced firing (AIF) and the present SF activity differ greatly. The distinction is as follows.…”
Section: Spontaneous Firing In An Anucleate Aml Axonal Segmentmentioning
confidence: 79%
See 3 more Smart Citations